2007
DOI: 10.1111/j.1349-7006.2007.00551.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress signaling in cancer

Abstract: The human body is continuously exposed to a wide variety of physical, chemical, and biological stress stimuli from both the external and internal environments. In order to adapt to or resist stress, cells are equipped with multiple signaling systems, which elicit a wide range of stress responses. Stress signaling also operates to eliminate cells with severe stress-induced damage through the induction of apoptosis. Once stress signaling is compromised in certain adverse conditions, however, cells exhibit aberra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Notably, melanoma in epidermis contains a high level of Nox4, but metastatic melanoma in lymph nodes exhibits a decrease in the Nox4 level. Elevated ROS production by up-regulated Nox enzymes may increase a risk of cancer in early stages by causing persistent proinflammatory responses (30). At least, Nox4 does not seem to contribute to the motile activity of melanoma cells, which is related to invasiveness of tumors (see Result).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, melanoma in epidermis contains a high level of Nox4, but metastatic melanoma in lymph nodes exhibits a decrease in the Nox4 level. Elevated ROS production by up-regulated Nox enzymes may increase a risk of cancer in early stages by causing persistent proinflammatory responses (30). At least, Nox4 does not seem to contribute to the motile activity of melanoma cells, which is related to invasiveness of tumors (see Result).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent evidence suggests that malonyl-CoA decarboxylase inhibition may be a potential novel target for cancer treatment [81]. Inhibition of FASN has been shown to induce endoplasmic reticulum stress in tumor cells [82], and a further mechanism of action may involve cooperation with endoplasmic reticulum stress inducers to enhance apoptosis [83]. In addition, ceramide accumulation following siRNA inhibition of FASN may have cytotoxic effects leading to tumor cell death in breast cancer cells (which can be rescued with inhibition of ceramide synthesis) [84].…”
Section: Mechanism Of Action Of Fasn Inhibitorsmentioning
confidence: 99%
“…Recently, it was reported that FASN inhibition induces endoplasmic reticulum stress in cancer cells, and FASN inhibitors cooperate with the endoplasmic reticulum stress inducer to enhance tumour cell death (Little et al, 2007). Considering the fact that tumour microenvironment stresses are strong inducers of the endoplasmic reticulum stress (Murakami et al, 2007), the FASN inhibitors could show selective and enhanced cytotoxicity to cancer cells under the tumour microenvironment conditions.…”
Section: Fasn and De Novo Fatty-acid Synthesis As Promising Targets Omentioning
confidence: 99%